Potensi Tandan Kosong Kelapa Sawit dan Bagas Sorgum Manis Sebagai Bahan Baku Energi Terbarukan - Wetri Febrina; Tatang H.Soerawidjaja; Ronny Purwadi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
The search for sources of renewable energy and raw materials became more intense with theincreasing demand for fossil fuels which is not balanced with the availability. Biogas is a renewable sourceof energy that can be produced from waste utilization agricultural and plantation products, such as emptyfruit bunches of oil palm and sweet sorghum bagasse. This study aims to assess the potential of oil palmempty fruit bunches and sweet sorghum bagasse as raw material source of biogas, biogas terms of theacquisition and the time to achieve maximum volume. The results showed that sweet sorghum bagassehas an advantage in the acquisition of biogas and time to achieve maximum volume, while oil palm emptyfruit bunches have advantages in terms of availability on the pitch, concurrently with increasing theproduction of crude palm oil in Indonesia. The conclusion from this study is that both oil palm bunches andsweet sorghum bagasse has potential as a raw material source of renewable energy, namely biogas butsweet sorghum bagasse has their advantages in terms of acquisition of biogas and the time to achievemaximum volume.Keywords: biogas, palm oil empty bunches, renewable energy, sweet sorghum bagasse